An Interplant Test of the Efficiency Wage Hypothesis - Cappelli, P.; Chauvin, K. (Quarterly Journal of Economics, 1991)
The analysis that follows tests the shirking model of efficiency wages by examining the relationship between rates of employee discipline and relative wage premiums across plants within the same firm. The structure of this data set controls for many of the problems that confound other tests of efficiency wage arguments, and the results suggest that greater wage premiums are associated with lower levels of shirking as measured by disciplinary dismissals. Shirking and discipline are also lower where conditions in the labor market raise the costs associated with shirking by making it more difficult to find alternative employment. It is less clear, however, whether the wage in this case is necessarily efficient in the sense of generating reductions in discipline sufficient to offset the costs of the wage premium.